Emotional intelligence and self-esteem in students from the city of Lima with and without participation in violence acts - Velásquez Centeno, Carlos M. (2003)
The present research has as objective, establishment the relationship between Emotional Intelligence (El) and self-esteem (SE), in an intentional sample of 10 14 secondary students from Lima Metropolitana, of both kinds, between 11 and 19 years old, with (n=510) who participate in violent acts and (504) who don't participate in violent acts, using two instruments: Escurra-Aparcana-Ramos Emotional Intelligence Test and Coopersmith Self-esteem Scale, remaining semantic and empirical adapted. The results yield between rnoderated and high correlation, with a significant between .01 and .05 in areas as Ernotional self Knowledge, Emotional Control, Self motivation, Empathy, Interpersonal relationship abilities and total Emotional Intelligence. These results let us measure the ability to perceive with precission, to estimate and to express emotions. While the relationship between Emotional Intelligence and Self-esteem are located in low and lowest standards with a significant standard between .01 and .05 demonstrating a bit independence between variables. The group of students who don't participate in violent acts demonstrated a greater Emotional Intelligence and Self-esteem than the group of students who participate in violent acts. Girls presents a greater Emotional Intelligence than guys, except in Self motivation where there are no difference by the kind in the motivation to get an objective. While in general Self-esteem, guys demonstrate a greater range than girls, determined by cultural factors.